Pengembangan Aplikasi Chatbot Untuk Layanan Pelanggan Berbasis Rule Bases Conversation - Norbertus Bili; Stefanus D.I.Mau; Paulus Mikku Ate (GLOBAL SCIENTS PUBLISHER, 2026)
Administrative information services at the Kalaki Kambe Village Office are an important part of supporting community needs, such as processing domicile certificates, cover letters, and other population documents. However, the service process is still carried out manually and is limited to village office working hours, causing various problems, including long queues, delays in information delivery, and high community dependence on village officials. Along with technological developments and the increasing public need for fast and flexible access to information, information technology-based solutions are needed that can improve the quality of public services. This study aims to design and build a chatbot application for village administrative information services using the rule-based conversation method. The research method used is a descriptive method with a software engineering approach, which includes the stages of needs analysis, system design, implementation, and application testing. Research data were obtained through interviews, observations, and documentation related to the administrative service process at the Kalaki Kambe Village Office. The results show that the developed chatbot application is able to provide information on village administrative file processing requirements automatically, structured, and accessible 24 hours a day. The application of the rule-based conversation method allows the chatbot to provide consistent responses and according to user needs based on predetermined rules and keywords. The existence of this chatbot can increase public information accessibility, reduce the workload of village officials due to repetitive questions, and support the creation of more effective and efficient public services. Therefore, the rule-based conversation chatbot application developed in this research can be used as an alternative solution for disseminating information on village administration services and has the potential to support digital-based public service transformation at the village level.